International Mask Festival Sebagai Instrumen Diplomasi Budaya Kota Surakarta Di Masa Pandemi Covid-19 - Fikri Ardiansyah, Kevin; Hatmini, Sritami Santi; Damayanti, Christy (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
This study aims to identify the International Mask Festival as an instrument of cultural diplomacy in Surakarta during the Covid-19 pandemic. The International Mask Festival which is held annually can establish cultural relations between nations. The emergence of the Covid-19 pandemic that hit the world had an impact on the cultural diplomacy activities of Surakarta City in 2020 & 2021. This research was conducted with a qualitative research method and the data search used was primary data in the form of interviews with the International Mask Festival secretariat and secondary data in the form of data from documents provided and referring to the concepts of cultural diplomacy and digital diplomacy. The results of this study show that the International Mask Festival is part of Surakarta City's cultural diplomacy instrument to promote culture and maintain a good image to the international community using digital media. Digital media is an alternative tool for the International Mask Festival in realizing its goals during the Covid-19 pandemic. In this case, the International Mask Festival held virtually through Youtube and Instagram is an innovation as an adaptation due to the Covid-19 pandemic that can reach a wider international community.